Studying the effect of the OsGATA rice transcription factor on salt stress tolerance in wheat - A. A. Verbitskaia; A. S. Egorova; E. A. Tsarkova; A. K. Gaponenko (Труды по прикладной ботанике, генетике и селекции)
This study shows the possibility of using the OsGATA rice transcription factor in transgenic lines of high-yielding wheat cultivars to increase their tolerance to salinity, which was confirmed using physiological and biochemical methods according to standard protocols. Wheat plants were grown in an artificial climate under optimal growing conditions. Genetic transformation methods were used to introduce the GATA gene into the genome of the used wheat genotypes. Transgenic lines were selected on selective media under in vitro conditions.The results of the experimental work showed that the expression of the GATA gene under salt stress may be responsible for the increased compartmentalization of Na+ in the vacuole, which provides improved salt tolerance. As a result of the experiment, collections of T1 transgenic wheat lines from cvs. ‘Zlata’, ‘Emir’ and ‘Agata’ expressing the GATA gene were obtained and studied for salt tolerance. Lines Zl.01, Zl.02, Zl.03 and Ag.02 were selected with PCR. Under NaCl salinity conditions, some of the transgenic lines showed a statistically significant increase in salinity resistance. The results of the study laid the foundation for studying GATA genes in wheat and for producing salinity-tolerant lines without growth defects or reduced productivity.